A Soft Switching Control Strategy Based on Interleaved Boost Converter for BLDC Motor Drive - V. Ramesh; Y. Kusuma Latha (Institute of Advanced Engineering and Science, 2015)
In this paper, Zero-Voltage-Transition (ZVT) two-cell interleaved boost Power Factor Correction (PFC) converter for voltage source Inverter (VSI) fed permanent magnet brushless DC motor (PMBLDCM) drive has been proposed Scheme reduce the torque ripple of BLDC motor drive and also reduce the switching losses of VSI for Which an auxiliary circuit is designed and added to the interleaved boost converter. For achieving soft switching, only one switch is used in auxiliary circuit which reduces the torque ripple and switching losses. In this proposed control strategy, the DC link voltage is controlled with interleaved boost converter which is proportional to the desired speed of the BLDC motor. In this paper, six switch and four switch VSI is also implemented with interleaved boost converter topology. A comparison is made between the six switch and Four Switch VSI fed PMBLDC Motor drive and Torque Analysis as been done. To validate the proposed work, results are presented. The results showed that proposed converter control strategy operating under soft switching mode improves the efficiency of the drive system with PFC feature in wide range of the speed control.